Risk-factors for antepartum fetal deaths in the city of São Paulo, Brazil Fatores de risco para mortes fetais anteparto no Município de São Paulo, Brasil - Marcia Furquim de Almeida; Gizelton Pereira Alencar; Hillegonda Maria Dutilh Novaes; Ivan França Jr; Arnaldo Augusto Franco de Siqueira; Oona M R Campbell; Daniela Schoeps; Laura Cunha Rodrigues (Universidade de São Paulo, 2007)
OBJECTIVE: To assess risk factors for antepartum fetal deaths. METHODS: A population-based case-control study was carried out in the city of São Paulo from August 2000 to January 2001. Subjects were selected from a birth cohort from a linked birth and death certificate database. Cases were 164 antepartum fetal deaths and controls were drawn from a random sample of 313 births surviving at least 28 days. Information was collected from birth and death certificates, hospital records and home interviews. A hierarchical conceptual framework guided the logistic regression analysis. RESULTS: Statistically significant factors associated with antepartum fetal death were: mother without or recent marital union; mother's education under four years; mothers with previous low birth weight infant; mothers with hypertension, diabetes, bleeding during pregnancy; no or inadequate prenatal care; congenital malformation and intrauterine growth restriction. The highest population attributable fractions were for inadequacy of prenatal care (40%), hypertension (27%), intrauterine growth restriction (30%) and absence of a long-standing union (26%). CONCLUSIONS: Proximal biological risk factors are most important in antepartum fetal deaths. However, distal factors - mother's low education and marital status - are also significant. Improving access to and quality of prenatal care could have a large impact on fetal mortality. OBJETIVO: Analisar os fatores de risco para óbitos fetais anteparto. METODOS: Estudo de caso-controle de base populacional realizado no Município de São Paulo, SP, de agosto de 2000 a janeiro de 2001. Os indivíduos foram selecionados a partir de uma coorte de nascimentos, obtida por meio de vinculação de declarações de nascimento e óbito. Os casos foram 164 óbitos fetais anteparto e os controles, uma amostra aleatória de 313 de sobreviventes até 28 dias. Foram realizadas entrevistas domiciliares com as mães e aplicado protocolo hospitalar. Foi empregada regressão logística para análise dos dados, baseado em modelo conceitual hierárquico. RESULTADOS: Os fatores estatisticamente significantes associados aos óbitos fetais anteparto foram: mães com união recente ou sem união; escolaridade da mãe inferior a quatro anos; nascimentos anteriores de baixo peso; mães com hipertensão, diabetes, e sangramento durante a gestação; ausência ou pré-natal inadequado presença de malformação congênita e presença de pequeno para idade gestacional. As maiores frações de risco atribuível na população foram inadequação do pré-natal (40%), hipertensão (27%), presença de pequeno para idade gestacional (30%), e ausência de união com mais de um ano (26%). CONCLUSÕES: Os fatores de risco proximais são os mais importantes para a mortalidade fetal anteparto. Entretanto, fatores distais como mães de baixa escolaridade e união recente ou ausente também desempenham importante papel. Melhorar acesso e qualidade do pré-natal pode promover impacto positivo na mortalidade fetal.